Adverse Outcome Pathway on Aryl hydrocarbon receptor activation leading to uroporphyria - Farhat, Amani (OECD Publishing, 2019)
Hepatic uroporphyria is a disorder where the disturbance of heme biosynthesis results in accumulation and excretion of uroporphyrin, heptacarboxyl- and hexacarboxyl porphyrin: collectively referred to as highly carboxylated porphyrins (HCPs). The disorder is due to a homozygous mutation in uroporphyrinogen decarboxylase (UROD), an enzyme involved in the heme biosynthesis pathway, or may be chemically induced, which involves the inhibition of UROD. This AOP describes the linkages leading to chemically induced porphyria through the activation of the aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor. AHR activation leads to the induction of cytochrome P450 1A2, a phase I metabolising enzyme, which in turn results in excessive oxidation of uroporphyrinogen. This oxidation produces a UROD inhibitor, preventing the conversion of uroporphyrinogen to coprouroporphyrinogen and increasing the synthesis of the UROD inhibitor in a positive feedback loop. The accumulation of uroporphyrinogen leads to its preferential oxidation and accumulation of HCP in various organs (Uroporphyria)
Keywords: Environment; Social Issues/Migration/Health